Exploring Affective Meaning in Indonesian TikTok News Comment Sections - Audrey, Nazzaura Kayla; Padang, Theofani Donita; Ginary, Intan Putri; Syafiq, M.; Ginting, Grace Chelvia (Ruang Kata, 2025)
This study analyzes affective meaning in the comment sections of Indonesian TikTok news accounts using Leech's (1981) semantic theory and Ekman's (1992) framework of six basic emotions: happiness, sadness, anger, disgust, surprise, and fear. The research aims to identify how TikTok users express emotions and attitudes toward news content through linguistic choices and emoji usage. A qualitative content analysis approach was employed, wherein twenty-five comments were collected through purposive sampling from five official news accounts: Inilah.com, Kumparan, Kompas TV, CNN Indonesia, and Detik.com. Data collection occurred between June and November 2025, focusing on videos with a minimum of ten million views. From each account, five of the most-liked comments were selected for semantic analysis. Both researchers independently analyzed the comments and compared interpretations to ensure reliability. The findings show that anger appeared most frequently (7 instances), followed by fear (6), sadness (4), disgust (4), happiness (2), and surprise (2). These results indicate that emotional responses on TikTok are often dominated by negative or serious feelings, reflecting users' sensitivity toward issues such as injustice, danger, and tragedy. Overall, the study concludes that affective meaning in TikTok comment sections not only represents individual emotions but also reflects collective empathy and cultural values within Indonesian digital discourse.